Analisis Nilai Perjuangan Dalam Film “Sejuta Sayang Untuknya” Karya Wiraputra Basri terhadap Relevansinya Agama Islam Modern - Siti Nurdiana; Ahmad Khumaidi; Yeniati Ulfah (Social Science Academic, 2026)
This study aims to analyze the representation of struggle values in the film Sejuta Sayang Untuknya and its relevance to modern Islamic education. The research employs a qualitative approach using semiotic analysis to examine meanings embedded in the film’s narrative, characters, and visual symbols. The findings indicate that the film represents parental struggle through values such as hard work, responsibility, sacrifice, patience, and compassion, which are constructed through cinematic elements that produce both denotative and connotative meanings and may develop into socially accepted interpretations. Furthermore, these values show strong relevance to the principles of modern Islamic education, particularly in character building based on amanah (responsibility), ṣabr (patience), ikhlāṣ (sincerity), and raḥmah (compassion). As an audiovisual medium, film is proven to be an effective learning tool as it integrates cognitive, affective, and reflective aspects of learners, thereby enhancing engagement, critical thinking skills, and contextual value internalization. Therefore, film can be utilized as an innovative and strategic pedagogical medium to support character education in the modern era.